Smart City Implementation in Bekasi City - Brigitta Michelle; Sushardjanti Felasari (Journal of Architecture & Environment, 2021)
The advancement of information and communication technology has had a major impact on the world as it increases the fulfillment of people's needs and comfort. This can be seen in urban development with the formation of the concept of a smart city, a city that integrates technological advances with people's lives to make effective decisions so as to improve the welfare of its people. This paper discussed the implementation of the smart city concept in Bekasi City, Indonesia. Along with its development, there are several applications of smart city elements in Bekasi City that are still far from expectations regarding the service quality and coverage. This study aims to see how smart city pillars are implemented in Bekasi City. Nonparticipant observation is used to conduct the study. The result shows that the range of smart city applications in Bekasi City is quite narrow and some service quality is still poor. Only 10 out of 21 criteria have been fulfilled in the city. This research needs further study on the implementation of smart cities in other Indonesian cities to see the effectiveness of its application and other solutions that can be offered.